Efeito da herbivoria por saúvas sobre a fenologia, sobrevivência, crescimento e conteúdo nutricional de árvores do Cerrado - Ribeiro, Fabiane Moreira Mundim (2009)
Herbivory often influences the fitness and development of attacked trees, acting as an important factor of evolutionary pressure on a species ecology. However, there are few studies that show the effects of insect herbivores on Cerrado tree species. In this study I evaluated the impact of the leaf-cutter ant Atta laevigata on the vegetative and reproductive phenology, survival, growth, architecture and leaf nutrients of six tree species of a Cerrado vegetation. For three years, I visited individuals of Cardiopetalum callophylum, Coussarea hydrangeaefolia, Guapira graciliflora, Maprounea guianensis, Vochysia tucanorum and Xylopia aromatica, and determined the intensity of phenological events and leaf-cutter ant attacks. In addition, based on the recurrence frequency and intensity of ant-attacks (often 100% of leaf removal) previously observed, I created two artificial defoliation experimental treatments that simulated high and low Atta laevigata s attack frequency. I then evaluated how the different frequencies of high intensity attacks influenced the survival, growth, flower production, leaf nutrient content and architecture of the trees. The results showed that the defoliation by leaf-cutter ants reduced the photosynthetic area of attacked trees and reduced flower and fruit production of preferred species. However, it did not affect the synchrony and timing of leaf and flower/fruit production. Herbivory frequency had a negative effect on the plant tolerance to herbivory, survival, flower production and architecture in all six species. However, for some species, the leaf content of N and P were significantly higher in defoliated trees than in control trees. These results indicated that leaf-cutter ants can be considered chronic herbivores in some areas of the Cerrado, and that their continued activities can, in the long-term, affect the structure and dynamics of the vegetation.